The response of Brahimi apple’s Cultivar to Foliar Application of Glycyrrhizin Extract (GLE) and Humic Acid (HA) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research team had conducted this work at a private orchard in Saqlawiya – Falluja district in 2019 toinvestigate the influence of foliar application of liquorice (glycyrrhizin) extract (GLE) and humic acid (HA)on some vegetative growth traits and yield of Al-Ibrahimi apple cultivar. The factorial experiment consistedof 2 factors; the first one was GLE which consisted of 3 levels (L0, L1, L2) of (0, 3, and 6 g.L-1) respectively;while the second one was HA with 4 levels (0, 2, 4, and 6 g.L-1) had symbols of (H0, H1, H2, and H3)successively. Thus, the total number of treatments was 12 of 3 replications. Every apple tree considered as anexperimental unit. The HA treatments were applied 7 times to soil every 20 days starting from 20th February2019 while the foliar applications of GLE were 5 times starting from the 1st April in the same year.A significant improvement in vegetative growth, quantity, and quality of yield due to GLE and HAapplications has been shown in increasing individual leaf area (LA), length of branches (LOB), number ofleaves (NOL), total chlorophyll content in leaves (TCL) , and total carbohydrates content in leaves (TCCL),average weight of fruits (AWF), and number of fruits per tree (NFT) that reflected positively on increasingyield per individual tree (YPT), total percentage of soluble solids (PSS), vitamin C content in fruits (CC) ,and decreasing acidity of fruits (TPA). The interaction between factors had significant influence in most ofstudied traits. Thus the L1H3, L2H2, and L2H3 treatment had the best results.
Keywords: Liquorice; Humic acid; Foliar application; Fruits; Apple; toxicity